2015
DOI: 10.1111/tog.12179
|View full text |Cite
|
Sign up to set email alerts
|

Constipation in pregnancy

Abstract: Constipation affects up to 38% of pregnancies. Rising progesterone levels in pregnancy contribute to slow gut motility. The standard clinical measures of chronic constipation are the Rome III criteria, which are based on frequency and difficulty in the passage of stool. Secondary constipation is due to primary disease of the colon (anal fissure, stricture and neoplasia), metabolic disturbances (hypothyroidism and hypercalcaemia) and neurological disorders. Severe constipation may result in faecal impaction, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 14 publications
0
19
0
4
Order By: Relevance
“…In this study, docusate sodium and potassium, as purgatives [32], were found in one of the examined products. The LC-UV and LC-MS ranges proved that sildenafil was used in the "fast slimming" product; while descriptions on the box only mentioned addition of herbs to increase sexual sensations.…”
Section: Resultsmentioning
confidence: 71%
“…In this study, docusate sodium and potassium, as purgatives [32], were found in one of the examined products. The LC-UV and LC-MS ranges proved that sildenafil was used in the "fast slimming" product; while descriptions on the box only mentioned addition of herbs to increase sexual sensations.…”
Section: Resultsmentioning
confidence: 71%
“…Among the participants in the present study, 40.4% of the pregnant women and 43.9% of the non-pregnant women did not have any opinion about the statement "Probiotic foods are helpful in preventing constipation". The scholarly literature reported that the rate of constipation during pregnancy ranged from about 11% to 38% (28). However, there are many studies proving that probiotics prevent constipation, a problem frequently encountered during pregnancy (29)(30)(31) Looking at the "Factors Affecting Women's Consumption of Probiotic Foods", the influence of health personnel on consumption of probiotics was minor (9.8%) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of the pelvic floor dysfunction, which can be seen in all ages, increases with age and paves the way for constipation (14). Constipation may emerge as a result of the inhibition of the motilin secretion due to an increase in the progesterone level particularly during pregnancy, and an increase in the renal and intestinal absorption of the water and sodium caused by the aldosterone, activated by the renin-angiotensin system, which is again induced by estrogen and progesterone (15). In our study, 68.2% of the participants were females.…”
Section: Discussionmentioning
confidence: 99%